Protection of Rights of Consumers in Business Transaction: A Comparative Approach with Special Reference to Islamic Law - Karim, Sheikh Mohammad Towhidul (IIUC Studies, 2016)
Consumer is weaker party in any business transaction. Islam has played a laudable role for the protection of consumer rights. The Islamic approach to business ethics is centered around criteria that are in common with stakeholder theory such as justice and balance, and includes unique additional criteria, such as, trust and benevolence. This article has given a comprehensive idea on the protection mechanisms of consumer rights in Islam. The promotion and protection of consumer rights are essential and considered as a prerequisite to right to life for every citizen. Consumer protection is necessary when markets fail to provide effective protection to the consumers or when there is an imbalance of power between buyers and sellers in a market. This paper examines the evolution of modern instruments and Islamic doctrine, and loopholes of conventional doctrine on consumer protection. Besides, this paper has explored how Islam brings unique benefits to all citizens for the protection of consumer?s rights. IIUC Studies Vol.10 & 11 December 2014: 183-200